2012
DOI: 10.1186/1471-2474-13-251
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for revision of primary total hip arthroplasty: a systematic review

Abstract: BackgroundNumerous papers have been published examining risk factors for revision of primary total hip arthroplasty (THA), but there have been no comprehensive systematic literature reviews that summarize the most recent findings across a broad range of potential predictors.MethodsWe performed a PubMed search for papers published between January, 2000 and November, 2010 that provided data on risk factors for revision of primary THA. We collected data on revision for any reason, as well as on revision for asept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
145
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(166 citation statements)
references
References 94 publications
(110 reference statements)
9
145
0
8
Order By: Relevance
“…The revision TKAs were mostly attributable to mechanical loosening and periprosthetic joint infection in younger patients (younger than 75 years), which may represent an emerging age shift, given that an increasing proportion of primary TKAs are being performed in younger patients [18,58]. The similar patient age trends in revision THA also may represent an emerging age shift in the burden of revision, given that an increasing proportion of primary THAs are being performed in younger patients [11,19,23,42,44]. It is estimated that by 2030, patients younger than 65 years will comprise 52% of primary THAs being performed [23].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The revision TKAs were mostly attributable to mechanical loosening and periprosthetic joint infection in younger patients (younger than 75 years), which may represent an emerging age shift, given that an increasing proportion of primary TKAs are being performed in younger patients [18,58]. The similar patient age trends in revision THA also may represent an emerging age shift in the burden of revision, given that an increasing proportion of primary THAs are being performed in younger patients [11,19,23,42,44]. It is estimated that by 2030, patients younger than 65 years will comprise 52% of primary THAs being performed [23].…”
Section: Discussionmentioning
confidence: 98%
“…The etiology of the increase in the number of revision procedures is multifactorial. The increasing absolute number of primary arthroplasties [21,44,53,58], expansion of the indications to include younger and more active individuals [11,18,19,23,29,30,34,42,44,46,49], and certain patient factors such as obesity [55,60], all likely contribute to overall revision rates. Projections based on population studies point to continued increases in the prevalence of revision procedures [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previously published studies focusing on THA in younger aged patients have reported successful pain relief, functional improvement, and implant survivorship with a variety of implant designs and bearing surfaces [9, 10, 12, 15-17, 22, 23, 33]. Although revision rates for THA have been reported more frequently among younger patients undergoing THA, it is difficult to determine whether the higher failure rate reflects demographic considerations for this group or failures of older implant systems or surgical techniques in this patient group [1,8,12,[24][25][26]. Among studies with well-performing contemporary cementless implants, wear of conventional polyethylene has been identified as the major cause of revision surgery or impending concern for younger patients who have undergone THA [6,15,16,32].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review conducted by Prokopetz et al (2012) investigated the risk factors for revision total arthroplasty after primary THA. The risk factors identified, which were consistent and statistically significant across the studies evaluated, included younger patient ages at the time of primary replacement, increased comorbidity, the presence of bone necrosis (rather than osteoarthritis) and the surgeon's experience (number of joint operations carried out) and larger femoral heads.…”
Section: J Reasons For Revision Total Arthroplastymentioning
confidence: 99%
“…The review does not state the size of the femoral head from which point the level of risk increases. In two of the three studies examined, the maximum femoral head size of the implanted femoral component was 28 mm (Prokopetz et al 2012). The review conducted by Prokopetz et al (2012) shows that alongside wear and tear, other factors such as the surgeons' experience constitute a significant risk of revision surgery.…”
Section: J Reasons For Revision Total Arthroplastymentioning
confidence: 99%